2021
DOI: 10.3389/fmats.2021.742195
|View full text |Cite
|
Sign up to set email alerts
|

Soliton Generation in Negative Thermal Expansion Materials

Abstract: Strain solitons have been observed statically in several 2D materials and dynamically in substrate materials using ultrafast laser pulses. The latter case relies on lattice relaxation in response to ultrafast heating in a light-absorbing transducer material, a process which is sensitive to the thermal expansion coefficient. Here we consider an unusual case where the sign of the thermal expansion coefficient is negative, a scenario which is experimentally feasible in light of rapid and recent advances in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…There have many materials which exhibit low and negative thermal expansion (NTE). [1][2][3][4][5][6] They have been of considerable interest due to potential application in tailoring coefficient of thermal expansion. ZrW 2 O 8 is an amazing material because it exhibits a relatively large isotropic negative thermal expansion (NTE) over a wide temperature range of −272.7 • C to 777 • C. [7,8] However, there are some problems in ZrW 2 O 8 .…”
Section: Introductionmentioning
confidence: 99%
“…There have many materials which exhibit low and negative thermal expansion (NTE). [1][2][3][4][5][6] They have been of considerable interest due to potential application in tailoring coefficient of thermal expansion. ZrW 2 O 8 is an amazing material because it exhibits a relatively large isotropic negative thermal expansion (NTE) over a wide temperature range of −272.7 • C to 777 • C. [7,8] However, there are some problems in ZrW 2 O 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies have shown that beams with high-order soliton structures are usually unstable in locally responsive media, and saturated nonlinear media cannot make beams with local structures, such as vortex beams, propagate stably, because the beams are prone to instability in the azimuth direction [23,24]. Although many materials exhibit non-local nonlinear properties, such as nematic liquid crystals [25], Bose-Einstein condensates [26], plasmas [27], thermally expanding materials [28], etc However, Snyder model is a simplified ideal model, and in real physical system, beam transmission will become more complex, and the theory and numerical simulation show that high-order solitons can not be stable transmission, so it is particularly important to explore the new model and study azimuth-modulated solitons.…”
Section: Introductionmentioning
confidence: 99%